Covalent Inhibition of Recombinant Human Carboxylesterase 1 and 2 and Monoacylglycerol Lipase by the Carbamates JZL184 and URB597 - Crow, J. Allen (2012)
Carboxylesterase type 1 (CES1) and CES2 are serine hydrolases located in the liver and small intestine. CES1 and CES2 actively participate in the metabolism of several pharmaceuticals. Recently, carbamate compounds were developed to inhibit members of the serine hydrolase family via covalent modification of the active site serine. URB597 and JZL184 inhibit fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), respectively; however, carboxylesterases in liver have been identified as a major off-target. We report the kinetic rate constants for inhibition of human recombinant CES1 and CES2 by URB597 and JZL184. Bimolecular rate constants (k(inact)/K(i)) for inhibition of CES1 by JZL184 and URB597 were similar [3.9 (±0.2) × 10(3) M(-1) s(-1) and 4.5 (±1.3) × 10(3) M(-1) s(-1), respectively]. However, k(inact)/K(i) for inhibition of CES2 by JZL184 and URB597 were significantly different [2.3 (±1.3) × 10(2) M(-1) s(-1) and 3.9 (±1.0) × 10(3) M(-1) s(-1), respectively]. Rates of inhibition of CES1 and CES2 by URB597 were similar; however, CES1 and MAGL were more potently inhibited by JZL184 than CES2. We also determined kinetic constants for spontaneous reactivation of CES1 carbamoylated by either JZL184 or URB597 and CES1 diethylphosphorylated by paraoxon. The reactivation rate was significantly slower (4.5x) for CES1 inhibited by JZL184 than CES1 inhibited by URB597. Half life of reactivation for CES1 carbamoylated by JZL184 was 49 ± 15 h, which is faster than carboxylesterase turnover in HepG2 cells. Together, the results define the kinetics of inhibition for a class of drugs that target hydrolytic enzymes involved in drug and lipid metabolism.